1993
DOI: 10.1542/peds.92.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Meningitis in Infants Younger Than 2 Years of Age: Acute Illness and Neurologic Complications

Abstract: Objective. We report the clinical features and cerebrospinal fluid (CSF) laboratory values for 277 children younger than 24 months of age with aseptic meningitis who were prospectively evaluated at three Baltimore hospitals between July 1986 and December 1990. A major objective was to define the incidence, etiology, and outcome of neurologic complications occurring during the acute illness. Methods. Cases were identified by surveillance in the ambulatory care departments of each of the three hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…(17)(18)(19)(20)(21)(22) This could be partially explained by the fact that the inflammatory response in the subarachnoid space as a result of bacterial infection is more severe than that due to viral infections. (23) The significantly higher frequency of ME complications among children less than one year of age is consistent with that reported by Gomes et al, (24) who reported that complications were more predominant among Brazilian children aged less than one year of age (71%). On the other hand, the significantly higher frequency of ME complications among exclusively breastfed children in their first six months of life in the present study is in agreement with the finding reported among Sudanese children by Salih et al, (25) who found a relation between the lack of exclusive breastfeeding and high frequency of complications following bacterial ME.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(17)(18)(19)(20)(21)(22) This could be partially explained by the fact that the inflammatory response in the subarachnoid space as a result of bacterial infection is more severe than that due to viral infections. (23) The significantly higher frequency of ME complications among children less than one year of age is consistent with that reported by Gomes et al, (24) who reported that complications were more predominant among Brazilian children aged less than one year of age (71%). On the other hand, the significantly higher frequency of ME complications among exclusively breastfed children in their first six months of life in the present study is in agreement with the finding reported among Sudanese children by Salih et al, (25) who found a relation between the lack of exclusive breastfeeding and high frequency of complications following bacterial ME.…”
Section: Discussionsupporting
confidence: 89%
“…(29) In children with viral ME, seizures were less frequent (13.9%), which is in agreement with those reported elsewhere. (21,23) Refractory seizures mainly result from damage to the cerebral cortex (hypoxia, infarctions, necrosis), and may also be exacerbated by other neurological (e.g. increased ICP, subdural effusion) or metabolic (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Infants may present with irritability, lethargy, poor feeding, vomiting, diarrhea, exanthems,and respiratory distress. 59 A sepsis screen can help rule out bacterial infection. The cerebrospinal fluid (CSF) study reveals aseptic meningitis in almost half of the infants with enterovirus infection.…”
Section: Clinical Manifestationsmentioning
confidence: 99%